2015
DOI: 10.1136/gutjnl-2014-308392
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAL regulates colorectal cancer progression by activating Wnt/β-catenin signalling pathway via suppression of activator protein 2α

Abstract: Our results suggest that CCAL is a crucial oncogenic regulator involved in CRC tumorigenesis and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
237
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(240 citation statements)
references
References 41 publications
2
237
0
1
Order By: Relevance
“…LncRNAs have been found to be frequently dysregulated in cancers and implicated in cancer stemness and chemoresistance (30,31). LncRNA-LET has been reported to be underexpressed in cancers of digestive system and associated with cancer metastasis (25,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been found to be frequently dysregulated in cancers and implicated in cancer stemness and chemoresistance (30,31). LncRNA-LET has been reported to be underexpressed in cancers of digestive system and associated with cancer metastasis (25,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the molecular mechanisms linked to CRC [6][7][8][9]. Tumor hypoxia is a pathological hallmark that may be correlated with metabolism, the activation of cell signaling, angiogenesis, differentiation, necrosis or cell apoptosis, tumor development and aggressiveness, etc [10][11][12].. Additionally, tumor hypoxia can have an adverse impact on the prognosis of some cancers (i.e., invasive breast cancer or cervical cancer) and the efficacy of chemo-and radiotherapy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…HOX transcript antisense RNA (HOTAIR), a lncRNA promoting tumorigenesis and metastasis cancers including HCC [74,75], could act as molecular scaffold for recruitment of histone methyltransferase such as complexes PRC2 and LSD1, then reprograms chromatin states by coupling histone H3K27 methylation and H3K4 demethylation to specify the pattern of histone modifications on target genes, suggesting a single lncRNA could act as an epigenetic modifying platform for distinct histone modification complexes simultaneously [76,77]. Noteworthy, the colorectal cancer-associated lncRNACCAL, depicted as a key regulator of the progression of colorectal cancer, might be induced by histone H3 methylation in colorectal cancer, further inferring the potential regulatory interplay of histone methylation and lncRNA in cancer [78].…”
Section: Long Noncoding Rna and Histone Methylationmentioning
confidence: 95%